San Francisco March for Peace in Central America and Equality in South Africa - Watkins, Howard::::::::: (1987)
Adam Watkins holding protest sign "Stop U.S. War in El Salvador" in front of Fresno banner; Sandy Iyall wearing red tennis shoes "Fresno Wants Peace in Central America + Equality in South Africa"